Siblings of Individuals With Eating Disorders: A Review of the Literature - Maon, Iris; Horesh, Danny; Gvion, Yari (Frontiers in Psychiatry, 2020)
Eating disorders (EDs) are serious psychopathologies characterized by a persistent disturbance in eating or eating-related behavior. Studies have shown EDs’ detrimental consequences not only for patients, but also for their families. Nevertheless, a specific group that has so far been neglected, in both the research and clinical fields, are siblings of individuals with EDs. In an effort to identify this population's needs, and to facilitate effective prevention and treatment, this paper aims to review the existing literature on the subject, and examine siblings’ personal experience, ways of coping, and levels of psychopathology. PubMed and PsycNet databases were searched with no publication date restrictions, yielding 26 relevant papers. Studies were categorized according to common themes they addressed, and subsequently summarized by highlighting common features, as well as information unique to each study. Several themes emerged, including emotional well-being, psychopathology, social consequences, family dynamics, and coping strategies. Results show that EDs experienced by one individual have significant effects on one's siblings, such as a decrease in quality of life, social isolation, and elevated familial strain. In several studies siblings were found to have elevated levels of psychopathology and EDs related symptoms. Nevertheless, findings’ nature and magnitude were highly varied. The review indicates the need for further studies that will examine possible intra- and interpersonal moderating factors for EDs’ impact on well-being among siblings, and take into consideration the substantial heterogeneity in studies conducted thus far. Additionally, this review highlights the need for novel and effective interventions, specifically targeting this at-risk group.